Study the Indian Judiciary's part in Ensuring domestic workers human rights (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Domestic workers are a vulnerable and underappreciated part of the workforce, and this research looks at how the Indian court has played a key role in protecting their human rights. Due to the informal nature of their employment and the absence of particular regulation, domestic workers often endure exploitation, abuse, and denial of fundamental rights, notwithstanding constitutional guarantees under Articles 14 and 21. Fair salaries, safe working conditions, and placement agency regulation are just a few of the topics that have been addressed in landmark court decisions that this study examines. This article discusses the efforts of the judiciary to provide domestic workers with legal safeguards, focusing on seminal decisions such as People's Union for Democratic Rights v. Union of India (1982). Social and cultural considerations, lack of legal education, and institutionalized prejudices are some of the obstacles that domestic workers confront while trying to get justice. It takes a look at judicial initiatives to promote social justice, bonded labour, and situations involving children as domestic workers. Despite the efforts of the court, the study shows that there are still major obstacles. To completely safeguard the human rights of domestic workers in India, it stresses the necessity of thorough legislation, systemic changes, and heightened awareness.